Implementasi Metode Up-Selling Pada Aplikasi Penjualan Online Berbasis E-Commerce - Agung Prabowo (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
UD. Berkah Profil is a manufacturer that produces home wall decorations and sells products such as concrete profile molds, natural stones and roster. Management has not implemented systems such as buying and selling transaction systems, marketing, promotions and offers. Therefore, to solve problems and find solutions in the Berkah Profil, it is necessary to create an e-commerce based online sales application on Berkah Profil to be used as a medium for spreading and expanding the marketing area and conduct buying and selling transactions 24 hours online. Then, the up-selling method is implemented in the developed application to create higher value offers with goods that are still related to the product chosen by the customer. By applying this method, the store manager gets the opportunity to make more profit. This research produces an e-commerce-based online sales application that uses the up-selling method to encourage potential consumers to get higher-value merchandise, and develops a system that is consistent with the waterfall model. Then, this application make it easier for potential consumers to search for goods and buy goods without having to travel for sales purposes.